The probabilistic cream rises: a longitudinal study of the relative age effect, relative age reversal and expertise across the youth to adult transition in elite European football players - Hendry, D.; Harvey, P.; Bilalic, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
The relative age effect is a well-established selection bias towards individuals born earlier within a selection year resulting in a disproportionate over representation of chronologically older players in talent development pathways. Despite over 20 years of research exploring this phenomenon across multiple domains, including football, longitudinal analysis are rare. In this study, we analyse over 5,000 elite male youth soccer players who participated in the UEFA Youth League over a ten year period. Player transfer market value and playing level were used as proxy measures of expertise and tracked longitudinally. Consistent with the RAE, we found that players born in the first quarter of the selection year (Q1) were almost four times more likely to be selected in comparison to those born in Q4. However, longitudinal analysis indicated a type of relative age reversal, as Q4 players went on to command higher transfer values across their careers and lower dropout compared to their Q1 peers. Yet, when we selected the best Q1 players to match the number of Q4 players, the Q1 players exhibited significantly better careers and remained in the sport longer. Findings provide partial support for relative age reversal and highlight inefficiencies in the talent development pathways.